113 WEIGHT GAIN AND FAT DISTRIBUTION WITH PIOGLITAZONE IN PATIENTS WITH TYPE 2 DIABETES ON INSULIN THERAPY. Issue 1 (1st January 2007) - Shah, P. K.; Mudaliar, S.; Aroda, V.; Wilson, J.; Chao, E.; Chang, A.; Skouse, J.; Burke, P.; Andre, M.; Henry, R. R.
Abstract : Background: Thiazolidinediones (TZDs) are widely used to treat type 2 diabetes (T2 DM). As PPAR-γ agonists, TZDs improve insulin sensitivity and glycemic control and have other beneficial nonglycemic effects. However, weight gain is an undesirable side effect and is of potential concern. Recent studies demonstrate that weight gain with TZD therapy is associated with an increase in subcutaneous adipose tissue (SAT) and a concomitant decrease in visceral adipose tissue (VAT). Insulin therapy alone is also associated with weight gain; however, body fat composition has not been studied with insulin therapy or with the additive effects of insulin and TZD therapy. Objective: To evaluate the effects of a pioglitazone and insulin combination versus insulin therapy alone on body fat distribution. Methods: We performed a randomized, double-blind placebo-controlled trial on 25 insulin-treated, obese T2 DM patients (BMI 36.5 kg/m 2, HbA1C 7.7%). Twelve patients were assigned pioglitazone (30 mg titrated to 45 mg) and insulin (PIO + INS) and 13 patients were assigned placebo and insulin (PLA + INS). Abdominal CT scans were performed before and after 12 to 16 weeks of treatment. VAT and SAT pre- and post-treatment and liver/spleen attenuation (L/S) ratios were measured (an L/S ratio < 1 represents fatty liver). Results: In the PLA-INS group, body weight increased from 108.7 to 110.1 kg ( p = .02), HbA1C decreased from 7.8 to 7.2% ( p = .02), SAT increased from 412.9 to 420.8 cm 2 ( p = .31), and VAT decreased from 266.6 to 250.5 cm 2 ( p = .17). In the PIO + INS group, weight increased from 107.1 to 112.0 kg ( p = .00), HbA1C decreased from 7.6 to 7.1% ( p = .03), SAT increased from 393.9 to 443.2 cm 2 ( p = .001), and VAT decreased from 240.3 to 223.8 cm 2 ( p = .13). When the two groups were compared, a significant increase in the SAT ( p = .01) and a trend toward decreased VAT was noted in the PIO + INS group compared with the PLA + INS group. Further, the L/S ratio in the PLA + INS group decreased from 1.08 to 1.04 ( p = NS) and increased from 0.999 to 1.075 ( p = .06) in the PIO + INS group, suggesting that pioglitazone combined with insulin decreases liver fat compared with insulin alone. Conclusions: In patients treated with insulin, at equivalent glycemia, the addition of pioglitazone is associated with increased SAT, decreased VAT, and decreased liver fat. These changes in body fat distribution could possibly contribute to the beneficial effects of the TZDs despite overall weight gain.